(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article describes the state of fertility of irrigated meadow-alluvial soils. It contains information on the morphogenetic indicators of meadow-alluvial soils, the amount of humus and nutrients. The amount of humus and nutrients in these soils was observed to be low during the research.